(untitled) (International Journal of Engineering and Computer Science, 2014)
Due to the extensive use of digital media applications, multimedia security and copyright protection has gained tremendous importance. Digital Watermarking is a technology used for the copyright protection of digital applications. In this project, a comprehensive approach for watermarking digital QR code image is introduced. We propose a hybrid digital media watermarking scheme based on Discrete Wavelet Transform (DWT) for a digital invisible watermarking is to embed binary image in the QR code image. In our method we embed a binary image considered as watermark embedded into one of selected wavelet subband. The proposed algorithm is also implemented on videos which is a novel approach compared to previous works based on the images. The experimental results show that our method has more robustness to attacks in different considerations and it can achieve a viable copyright protection and authentication.